Case Report on Hemangioma - Porwal, Surya; Bhatia, Gouri; Attresh, Gyanander; Batra, Jitender; Garg, Balram; *, Kirtika (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Vascular anomalies comprise a widely heterogeneous group of tumours and malformations. Haemangioma is the most common benign tumour of vascular origin of head and neck region most commonly found on lips, tongue, buccal mucosa and palate. Despite of its benign origin and behaviour, it is always of clinical importance to the dental profession and requires appropriate management. This case of palatal haemangioma mimicked itself as multiple palatal abscesses on visual examination that lead to the confusion. The objective of this case report is to create awareness and familiarity to such an unusual presentation so that the lesion can be diagnosed and managed appropriately. This case report brings out a new dimension to a periodontist, the way a haemangioma can present and the importance of appropriate diagnosis and management, as haemangioma can lead to a life threatening bleeding.